Structural Properties of Graphene - Shrestha, Sanju; Thapa, Shanti; Pandey, Bed Prasad (Pragya Darshan प्रज्ञा दर्शन, 2023)
Graphene, a flat monolayer of carbon atoms tightly packed into a two-dimensional (2D) honeycomb lattice with six carbon atoms, are of two types due to their bonding. Due to its structural uniqueness, properties of the grapheme is found to be very different and important in application point of view. Hence, the authors have studied the structural properties as co-ordination number, coordinates, distances of nearest atoms from 1st to 5th, analytically using two dimensional coordinate system taking one atom of a unit cell at the origin. Furthermore, packing fraction is also calculated, as the property is very important to study absorption/adsorption of different atoms into the sheet of it.